The effects of hydrated C(60) fullerene on gene expression profile of TRPM2 and TRPM7 in hyperhomocysteinemic mice. (August 2014) - Etem, Ebru Onalan; Bal, Ramazan; Akağaç, Arzu Etem; Kuloglu, Tuncay; Tuzcu, Mehmet; Andrievsky, Grigory V.; Buran, Ilay; Nedzvetsky, Victor S.; Baydas, Gıyasettin
Abstract Background: Hyperhomocysteinemia (HHcy) is associated with neurodegenerative diseases. Transient receptor potential melastatin (TRPM2) and TRPM7 channels may be activated by oxidative stress. Hydrated C(60) fullerene (C(60)HyFn) have recently gained considerable attention as promising candidates for neurodegenerative states. We aimed to examine the effects on TRPM2 and TRPM7 gene expression of C(60)HyFn due to marked antioxidant activity in HHcy mice. Methods: C57BL/6 J. mice were divided into four groups: (1) Control group, (2) HHcy, (3) HHcy + C(60)HyFn-treated group and (4) C(60)HyFn-treated group. TRPM2 and TRPM7 gene expression in brains of mice were detected by real-time PCR, Western blotting and immunohistochemistry. Apoptosis in brain were assessed by TUNEL staining. Results: mRNA expression levels of TRPM2 were significantly increased in HHcy group compared to the control group. C(60)HyFn administration significantly decreased serum levels of homocysteine and TRPM2 mRNA levels in HHcy + C(60)HyFn group. Whereas, HHcy-treatment and C(60)HyFn administration did not change the expression of TRPM7. Conclusion: Administration of C(60)HyFn in HHcy mice significantly reduces serum homocysteine level, neuronal apoptosis and expression level of TRPM2 gene. Increased expression level of TRPM2 induced by oxidative stress might be involved in the ethiopathogenesis of HHcy related neurologic diseases.